Clinical and histopathological study of different degrees of endometrial hyperplasia - Gordillo delboy, R. (2015)
In this paper we propose to make a description of the different degrees of endometrial hyperplasia in relation to the clinic. We consider grades not as independent "forms" but as mere clinical-morphological aspects that have been separated for better analysis and interpretation.